GAMBARAN GINGIVITIS PADA IBU HAMIL (STUDI LITERATUR) (Jurnal Kesehatan Siliwangi, 2021)
Maintenance of oral health is important during pregnancy. Gingivitis during pregnancy is caused by an increase in the concentration of the hormon estrogen and progesterone. Gingivitis is one that is highly susceptible to periodontal disease occurs when the maintenance of oral health in pregnant women is not properly maintained. This study aims to determine the description of the gingivitis in pregnant women. Knowledge and actions to maintain dental and oral health in pregnant women greatly determine the status of the oral cavity and the health of pregnant women and their fetuses. This kind of research represents a study of literature. Data collection from Community Health Center in Garut was then analyzed using content analysis method. The results of secondary data collected and analyzed showed that pregnant women experienced more gingivitis in the first trimester in the first posyandu and second posyandu areas due to congenital hormonal factors in pregnant women. The Community Health Center is expected to further improve the dental and oral health service program for pregnant women such as promotive activities about the importance of maintaining oral health and hygiene during pregnancy, giving motivation and advice to pregnant women to check their oral health at the dentist at the same time during their pregnancy check-up.